Proceedings of the Anti-Phishing Working Groups 2nd Annual eCrime Researchers Summit 2007
DOI: 10.1145/1299015.1299021
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of machine learning techniques for phishing detection

Abstract: There are many applications available for phishing detection. However, unlike predicting spam, there are only few studies that compare machine learning techniques in predicting phishing. The present study compares the predictive accuracy of several machine learning methods including Logistic Regression (LR), Classification and Regression Trees (CART), Bayesian Additive Regression Trees (BART), Support Vector Machines (SVM), Random Forests (RF), and Neural Networks (NNet) for predicting phishing emails. A data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
178
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(197 citation statements)
references
References 10 publications
3
178
0
3
Order By: Relevance
“…Abu-Nimeh et al [9] adopted the bag-of-words strategy and used a list of words frequently found on phishing sites as features to detect phish, which is not expressive and easy to defeat by attackers. In [16], Ludl et al came up with a total of 18 properties solely based on the HTML and URL.…”
Section: Methods For Automatic Phish Detectionmentioning
confidence: 99%
“…Abu-Nimeh et al [9] adopted the bag-of-words strategy and used a list of words frequently found on phishing sites as features to detect phish, which is not expressive and easy to defeat by attackers. In [16], Ludl et al came up with a total of 18 properties solely based on the HTML and URL.…”
Section: Methods For Automatic Phish Detectionmentioning
confidence: 99%
“…PFILTER, which was proposed by Fette et al [8], employed SVM to distinguish phishing emails from other emails. According to [9], Abu-Nimeh et al compared the predictive accuracy of several machine learning methods including LR, CART, RF, NB, SVM, and BART. They analyzed 1,117 phishing emails and 1,718 legitimate emails with 43 features for distinguishing phishing emails.…”
Section: Related Workmentioning
confidence: 99%
“…They analyzed 973 phishing emails and 3,027 legitimate emails with 12 features, and showed that the lowest error rate was 2.01%. The experimental conditions were different between [9] and [10], however, the machine learning provided high accuracy for the detection of phishing emails.…”
Section: Related Workmentioning
confidence: 99%
“…In spite of this challenge, classifiers have been shown to achieve good precision in identifying phishing messages, over collections containing typical phishing messages [6,3,1], using features which are often unnoticed by (human) victims, e.g. hyperlinks to suspect websites in the email.…”
Section: Design Of An Integrated Email Filtering Systemmentioning
confidence: 99%